PENGEMBANGAN ILMU FIKIH DALAM PERSPEKTIF FILSAFAT ILMU - Lina Kushidayati; Agus Fakhrina; Iman Fadhilah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Fiqh has always been an important aspect in the live of Muslims. In the beginning of Islam, Muslim did not face problems as experienced by the later generations of Muslims therefore Muslims need to develop fiqh in accordance with  the  current  situation. In this case, philosophy may provide a new perspective in the development of fiqh. This article discusses about historical development of fiqh and how philosophy contributes to it.Keywords: fiqh, philosophy, development